Anti-GAD Antibody-associated Syndrome Presenting with Limb Myoclonus. (1st November 2018) - Manzke, Pedro; Grippe, Talyta; Tavares, Georgia L.; Leal, Lucas C.; Roze, Emmanuel; Apartis, Emmanuelle; Maciel Dias, Ronaldo; Ferreira, André G. F.
Background: The clinical spectrum of anti-glutamic acid decarboxylase (GAD) antibody-associated neurologic syndromes is expanding, with focal, generalized, and atypical forms. Case Report: We describe a 59-year-old female showing continuous right lower limb myoclonus and mild encephalopathy. These symptoms started 2 weeks prior to evaluation. The patient had great improvement with intravenous steroids. An autoantibody panel was positive for anti-GAD. Discussion: Various clinical manifestations, including myoclonus, may relate to anti-GAD antibodies. The treatment options available include symptomatic drugs, intravenous immunoglobulin, steroids, and other immunosuppressant agents.